MATHEMATICAL MODELING APPROACH FOR EMERGENCY EDUCATION OF REFUGEES IN DEVELOPING COUNTRIES - Macİt, Betül and Demİrel, Neslihan and Demİrel, Eray and Gökçen, Hadi (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
It is very important to increase the efficiency of humanitarian logistics (HL) operations during the post-disaster phase in order to avoid human and economic losses. In this paper, two mathematical models have been developed to fulfill the educational needs of refugees in developing countries. Two different policies based on additional placement or planning of a double-shifting system in existing schools and opening new temporary education centers in terms of efficient use of scarce resources (funds) and enrollment of more refugees into the education system have been examined. The proposed models have been shown in a real-life case. In the first model, 1130 children cannot access education because of the capacity constraints and maximum coverage distance, while in the second model, the number of unschooled children is increased by 426. Results show that the main problems are the capacity shortage in existing schools and the insufficient budget for opening new schools.